2020
DOI: 10.1016/j.jot.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite-element analysis of aggravating medial meniscus tears on knee osteoarthritis

Abstract: BackgroundThe biomechanical change during the medial meniscus damage in the process of knee osteoarthritis has not been explored. The purpose of this study was to determine the effect of aggravating medial meniscus degenerative tear on the progress of knee osteoarthritis through the finite-element simulation method.MethodsThe three-dimensional digital model of a total-knee joint was obtained using a combination of magnetic resonance imaging and computed tomography images. Four types of medial meniscus tears we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 40 publications
(45 reference statements)
2
48
0
5
Order By: Relevance
“…In biomechanics research, the contact position, contact area and contact stress between joint surfaces are often measured. At present, there are a variety of experimental measurement methods for joints, including 3D photoelastic measurement, pressure sensing and finite element analysis [26][27], but these methods have a large error in the measurement of joint stress and the operation method is relatively complex. Therefore, we choose pressure-sensitive film technology, which can not only directly measure the pressure value, but also can measure the contact area, intuitively see the distribution of pressure, has obvious advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In biomechanics research, the contact position, contact area and contact stress between joint surfaces are often measured. At present, there are a variety of experimental measurement methods for joints, including 3D photoelastic measurement, pressure sensing and finite element analysis [26][27], but these methods have a large error in the measurement of joint stress and the operation method is relatively complex. Therefore, we choose pressure-sensitive film technology, which can not only directly measure the pressure value, but also can measure the contact area, intuitively see the distribution of pressure, has obvious advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal cohort study using population-based healthcare data from Sweden, Snoeker et al [ 8 ] reportedthat meniscal tear increased the risk of future diagnosed knee OA. Through 3D finite-elemental analyses, Li et al [ 9 ] demonstrated meniscal injury leads to biomechanical changes that can accelerate the progression of knee OA, and they found meniscectomy can relieve symptoms but increases the incidence of osteoarthritis. Because of the high incidence of discoid lateral meniscus [ 10 12 ], corresponding morphological research has been published [ 6 , 13 , 14 ], but little attention was paid to the medial side.…”
Section: Discussionmentioning
confidence: 99%
“…In biomechanics research, the contact position, contact area and contact stress between joint surfaces are often measured. At present, there are a variety of experimental measurement methods for joints, including 3D photoelastic measurement, pressure sensing and nite element analysis [28][29], but these methods have a large error in the measurement of joint stress and the operation method is relatively complex. Therefore, we choose pressure-sensitive lm technology, which can not only directly measure the pressure value, but also can measure the contact area, intuitively see the distribution of pressure, has obvious advantages.…”
Section: Discussionmentioning
confidence: 99%